Efficiency of back pain-school program in the treatment of patients with chronic mechanical back pain [Mekanik özellikte kronik bel ağrısı olan hastaların tedavisinde bel ağrısı okulu programının etkinliği] - (:unkn) unknown (Marmara University, 2014)
Objective: The aim of the study was to investigate the efficiency of back pain-school programs in the treatment of patients with chronic mechanical back pain. Patients and Methods: Fifty nine (35 females, 24 males) patients diagnosed with chronic mechanical back pain were divided into two groups. Both groups received traditional physical therapy consisting of hot pack, conventional transcutaneous electrical nerve stimulation (TENS), therapeutic ultrasound, Williams and mobilization exercises for three weeks (15 sessions). Patients in the 1st group received back pain-school program in addition. Patients were evaluated for pain (Visual Analogue Scale), depression (Beck Depression Scale) and functional disability (Oswestry Disability Index) before, after and 4 weeks after the treatment. Results: Pain scores were significantly reduced after treatment and in the follow up assessments (p=0.000) in the back painschool group. The depression scores did not differ significantly in both groups. Functional disability improved in the back painschool group (p=0.000). The back pain-school group had superior results in pain and function scores in the follow up assessment. Conclusion: Attending the back pain-school program in addition to traditional physical therapy in the management of patients with chronic back pain has positive effects on improving pain and function, especially in the long term. © 2014, Marmara University. All rights reserved.
Keywords: Back pain-school; Chronic back pain; Physical therapy